Slow Fault Slip Signatures in Coseismic Ionospheric Disturbances - Heki, Kosuke; Bagiya, Mala S.; Takasaka, Yuki (My University, 2022)
Rise times of earthquake moment release influence the spectra of seismic waves. For example, slow fault movements in tsunami earthquakes excite larger tsunamis than expected from intensities of short-period seismic waves. Here we compare amplitudes of two different atmospheric waves, long-period internal gravity waves and short-period acoustic waves, excited by coseismic vertical crustal movements. We observe them as coseismic ionospheric disturbances by measuring ionospheric electrons using global navigation satellite systems. Four regular megathrust earthquakes Mw 8.0â€“9.0 showed that the internal gravity waves become ten times stronger as the magnitude increases by one. We found that the 2010 Mentawai earthquake, a typical tsunami earthquake, excited internal gravity waves stronger than those expected by this empirical relationship. On the other hand, amplitudes of acoustic waves excited by tsunami earthquakes were normal. This suggests that slow fault ruptures excite long-period atmospheric waves efficiently, leaving a slow earthquake signature in ionospheric disturbances. Plain Language Summary Rapidly moving objects excite short-period waves, and slow objects excite long-period waves. We confirmed this for atmospheric waves excited by vertical crustal movements associated with large earthquakes. Two kinds of atmospheric waves, long-period internal gravity waves and short-period acoustic waves, propagate upward hundreds of kilometers and disturb the Earthâ€™s ionosphere. They are observed by receiving dual-frequency microwave signals from satellites. We compared atmospheric wave amplitudes excited by ordinary earthquakes and by â€œtsunamiâ€ earthquakes, characterized by slow fault movements. We found that the 2010 Mentawai earthquake, a typical tsunami earthquake, excited abnormally large internal gravity waves from ionospheric observations. This is the first slow earthquake signature found in space.
Keywords: Slow earthquake; Ionospheric disturbance; Internal gravity wave; Acoustic wave; Tsunami earthquake; GNSS-TEC